A Phenomenological Study of Barriers to Smoking Cessation among Patients with Chronic Obstructive Pulmonary Disease in Malaysia - Md Khairi, Lukman Nul Hakim; Wan Zakaria, Wan Aimuni; Mukhtar, Mazlina; Sopi, Muhammad Fais; Gnanasan, Shubashini; Samsudin, Azlina (Journal of Pharmacy, 2026)
Introduction: Smoking cessation is an essential intervention for chronic obstructive pulmonary disease (COPD) patients who still smoke. However, many patients struggle to quit successfully. Understanding the barriers they face is crucial to improving cessation strategies. Objectives: This study aimed to explore the real, often overlooked challenges COPD patients face when trying to quit smoking. Methods: A phenomenological study was conducted with a purposive sample of 11 male participants (GOLD 2, FEV1 46–75%) recruited from the Respiratory Clinic of Hospital Sultanah Nur Zahirah, Kuala Terengganu, Terengganu. Patients who were unable to stop smoking despite receiving treatment for COPD were included. The interviews were audio-recorded, transcribed verbatim, and thematically analysed using the Atlas.ti 23 software. Trustworthiness was ensured through member checking, reflexivity, and audit trails. Results: Three themes emerged: (1) Engagement with assisted smoking cessation, hindered by systemic referral gaps and misconceptions; (2) Requiring support while maintaining autonomy, where fear of mockery led to social isolation; and (3) Motivational factors, characterised by unstable motivation and a complacency window where low symptom burden diluted the urgency to quit despite objective lung function decline. Conclusion: COPD patients face unique barriers where clinical severity and subjective discomfort intersect. Factors like disconnect from formal healthcare services, fatalistic resignation (redha), and social policing by families force patients into a solitary, unsustainable struggle. Cessation strategies must bridge these clinical and cultural gaps by aligning with the patient’s specific disease stage and sociocultural context.